POTENSI PENGEMBANGAN JAGUNG PULUT MENDUKUNG DIVERSIFIKASI PANGAN / Potency of Waxy Corn Development to Support Food Diversification - Suarni Suarni; Muh. Aqil; Herman Subagio (Badan Penelitian dan Pengembangan Pertanian, 2019)
The success of staple food diversification can contribute to reduce rice consumption and encouraging national food self-sufficiency. Among food crops commodities, corn provide a potential to support local food based diversification. The type of corn that is preferable by consumer is white/waxy corn. Kernel color of waxy corn consists of white, yellow, purple, and black. Waxy corn can be harvest since the mild stage to anticipate food and malnutrition and make it more superior than other cereals. Corn processed into various products by using traditional, semi-traditional, and food industry products with specific superiority. Waxy corn is currently available in the market such as local varieties and newly released varieties such as Pulut URI-1 and Pulut URI-2. The market opportunity of waxy corn-based products in Indonesia has a more competitive advantage than before due to the change of lifestyle and food dietary. Promotion of waxy corn technologies needs to be done quickly to the related stakeholders including farmers, snacks producers, and businessman of waxy corn-based products to enhance the adoption of this commodity to support food diversification.Keywords: Waxy corn, food diversification, development AbstrakKeberhasilan diversifikasi pangan pokok berdampak terhadap pengurangan konsumsi beras sehingga mendorong keberlanjutan swasembada pangan. Salah satu komoditas yang dapat dimanfaatkan untuk diversifikasi pangan adalah jagung. Di antara beberapa jenis jagung yang berkembang, jagung pulut disukai oleh banyak konsumen. Jagung pulut memiliki warna yang beragam mulai dari putih, kuning, ungu, hingga hitam. Jagung pulut dapat dipanen muda atau lebih awal sehingga dapat mengantisipasi kerawanan pangan dan gizi. Hal ini menjadikan jagung pulut lebih unggul dibanding komoditas serealia lainnya. Berbagai produk olahan pangan dapat dihasilkan dari jagung pulut, mulai dari tradisional, semi tradisional, dan hingga modern, masing-masing memiliki nilai tambah tersendiri. Varietas jagung pulut telah tersedia, baik lokal maupun varietas unggul baru (URI-1 dan URI-2). Peluang pasar pangan berbasis jagung pulut di Indonesia makin terbuka seiring dengan perubahan gaya hidup dan pola makan konsumen yang mengarah pada hidup sehat. Dalam upaya pengembangan diversifikasi pangan perlu disosialisasikan paket teknologi budi daya dan pengolahan jagung pulut kepada masyarakat luas, terutama petani, pengrajin makanan, dan pebisnis produk pangan.Kata kunci: Jagung pulut, diversifikasi pangan, pengembangan